The Impact of Budget, CSR, and Transparent Communication on Community Support: The Mediating Role of Satisfaction at PT. Penajam Banua Taka Harbor - Susiyanti, Wiwik; Hasniaty, Hasniaty; Rukaiyah, St. (Universitas Negeri Gorontalo, 2024)
Purpose: This research aims to explore and analyze PT's implementation of budgeting, CSR programs, and communication transparency. Pelabuhan Penajam Banua Taka towards community support through community satisfaction in executing social and environmental responsibility programs.Design/Methodology/Approach: The study was conducted among the beneficiaries of CSR programs implemented by PT—Pelabuhan Penajam Banua Taka, with data collected through questionnaire distribution. The research population consisted of 700 beneficiaries during 2020, 2021, and 2022, with 254 respondents selected as samples using the Stratified Random Sampling technique. Data analysis employed quantitative descriptive analysis and the Structural Equation Modeling (SEM) method with Partial Least Squares (PLS) as the analytical tool. The SEM PLS method was utilized to test and model the complex relationships among variables in the study.Findings:The results indicate that budget implementation significantly contributes to community satisfaction, while CSR and communication transparency directly influence community satisfaction. Although the relationship between CSR and community support is not significant, community satisfaction plays a strong mediating role in connecting these factors. The implication is that companies need to continuously strengthen budget implementation, enhance CSR programs, and ensure communication transparency to build more solid community support.